BOOK REVIEW OF JONATHAN STROUD’S LOCKWOOD & CO.: THE SCREAMING STAIRCASE - HAQQI, HIBATUL (LANTERN (Journal on English Language, Culture and Literature), 2016)
Literature is an artwork from the expression of human’s feeling and mind. One example for that artwork is novel. There are many novels that human has produced. With different theme, style and storyline, novel becomes a material reading in human world, especially for entertainment. In Theory of Literature, Wellek and Warren state, “Literature cannot be ‘studied’ at all. We can only read, enjoy and appreciate it. Overall, we can only accumulate all kinds of information about literature” (1948:15). With that many themes of the novels that human has made, one of the themes that are interesting is horror. Horror usually has connection with mysterious things. With those mysteries, people will get the atmosphere, the feeling and the thought of the story. Sometimes, they will get the terror of the horror itself and make them shudder. They will try to solve the case while reading it as well. Even though, some unexpected accidents that happen will break the assumptions they have made as they read the novel.